Role of immune cells in mediating the effect of gut microbiota on Hashimoto’s thyroiditis: a 2-sample Mendelian randomization study - Pei, Xiao-Qing; Wang, Wen-Hao; Gao, Yue-Hua; Zhang, Tong-Xin; Liu, Jing-Yu; Zhao, Zhen-Dan; Zhang, Hua-Wei (Frontiers in Microbiology, 2024)
Purpose: Hashimoto's thyroiditis (HT) is one of the most commonly encountered types of autoimmune thyroid disorders (AITDs), influenced by environmental factors, genetics, and the immune system. Previous research has shown a correlation between gut microbiota and HT, as well as the involvement of immune cells in its onset and progression. We aim to investigate whether immune cells act as intermediaries in the causal relationship between gut microbiota and HT.Methods: In this study, we conducted bidirectional two-sample Mendelian randomization (MR) analyses for gut microbiota and HT from genome-wide association study (GWAS) data. Subsequently, MR analyses were performed for 731 immune cells and gut microbiota, from the MiBioGen study, followed by MR analysis for HT and 731 immune cells, derived from the GWAS dataset comprising 3,757 European subjects, providing insights into the impact of 22 million variants on 731 immune cell signatures.Results: There is a causal relationship between the increase in the number of 15 gut microbiota and HT. We observe that genus. Akkermansia, family.Alcaligenaceae, family.Desulfovibrionaceae, family.Verrucomicrobiaceae, class.Verrucomicrobiae, order.Verrucomicrobiales, phylum.Verrucomicrobia, class.Alphaproteobacteria, order.Desulfovibrionales, genus.Ruminococcus torques group, genus.Butyrivibrio, and genus.Coprococcus3 is negatively correlated with HT. Additionally, genus.Intestinimonas, genus.Turicibacter, and genus.Anaerostipes are positively correlated with HT. We identify EM CD4+Tcell as the mediator between gut microbiota and HT.In conclusion, we present causal associations between EM CD4+Tcellmediated gut microbiota and HT, as inferred from MR findings derived from extensive aggregated GWAS and GWAS data. Our research offers guidance and direction for treating and preventing HT.